Analysis Stability of Retaining Wall type Soldier Pile during Dewatering Work on Hospital Construction Site - Ramadhani, Yulia Putri; Solin, Dian; Kahaditu, Yerry; Le, Hoang-Khanh (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Groundwater subsidence during dewatering work can be a serious challenge if soil conditions are unstable, potentially disrupting the stability of supporting structures such as soil retaining walls. This research analyzed the stability of soldier pile type soil retaining walls during the dewatering process in hospital construction projects in the BSD area. The data used included the results of Standard Penetration Test (N-SPT), monitoring of dewatering work, inclinometer readings, and stability analysis using a 2D-based finite element software. The simulation results showed that the decrease in the groundwater level caused a change in lateral pressure on the retaining wall, with the maximum deformation reaching 2 m and the safety factor dropping from SF = 2.5 to SF = 2.2. If the analysis indicates a critical impact on stability (SF < 1.5 or deformation exceeding tolerances), then mitigation measures such as the installation of additional struts or dewatering system optimization are required. These findings provide technical guidance to minimize the risk of structural failure during the dewatering process on softsoils.